The life evaluation by linear cumulative damage rule for cold dwell fatigue of Ti‐6Al‐4V alloy. Issue 1 (28th October 2021) - Ota, Yutaro; Kubushiro, Keiji; Yamazaki, Yasuhiro
Abstract: Low cycle fatigue (LCF) life at ambient temperature of Ti alloys is well known to decrease with stress dwell. This phenomenon, called cold dwell fatigue (CDF), is influenced by the peak stress, dwell time, and microstructure. For this study, the CDF life was evaluated by the linear cumulative damage rule. The influence of test conditions and microstructure on the linear cumulative damage rule was also verified. By the linear cumulative damage rule, when creep damage is calculated using the time exhaustion rule, theCDF damage was evaluated by the inequality of D Total = ( D F, D C ) ≤ (0.01, 10 −6 ). However, the CDF damage can be evaluated in the range of D Total = 0.6–1.2 when creep damage was calculated using the ductile exhaustion rule. Results indicate that the evaluation was almost independent of the dwell time, peak stress, and microstructure, so it is also a versatile method for evaluating CDF responses. Highlights: The stress sensitivity of the cold dwell fatigue (CDF) test was higher than that of the low cycle fatigue (LCF) test. Fracture mode was depended on dwell time and peak stress. In the linear cumulative damage rule, when D C was calculated using the time exhaustion rule, the creep–fatigue damage was organized by the inequality D Tota l = ( D F, D C ) ≤ (0.1, 10 −6 ). When D C was calculated using the ductility exhaustion rule, the creep–fatigue damage was organized in the range of D Tota l = 0.6–1.2.